The Effect of China's National Essential Medicine Policy on Health Expenses: Evidence From a National Study - Qian Li PhD; Fei Chen PhD; Min Yang MD; Liyong Lu MSc; Jay Pan PhD; Xiaosong Li PhD; Qun Meng PhD (SAGE Publishing, 2018)
To increase use of medical service across the country, the Chinese government has tried to improve equity in health care access and reduce patients' medical expenses. For this purpose, the National Essential Medicine Policy (NEMP) was introduced in 2009 to mandate the distribution of medicines to health care facilities at a low cost and without profit. This study aims to evaluate the effect of the essential medicine policy on average per-visit expenses for outpatient and inpatient services. The annual national surveillance system data covering all the grassroots-level primary health care facilities (PHFs) in 2675 counties and 31 provinces in China during 2008 to 2012 were used in this study. The 4-level hierarchical random effects models were utilized to deal with possible dose-response effects of the policy and possible variations of such effects at the provincial, county, and facility levels. Our research findings suggest that the NEMP had positive effects in reducing both outpatient and inpatient expenses at grassroots level, and the policy effects tended to be greater as the exposure time increased. This study provides implications on reforming China's health system and its medicine cost control policies.